2008
DOI: 10.1074/jbc.m706069200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Mevalonate and Methylerythritol Phosphate Pathways to the Biosynthesis of Dolichols in Plants

Abstract: Plant isoprenoids are derived from two biosynthetic pathways, the cytoplasmic mevalonate (MVA) and the plastidial methylerythritol phosphate (MEP) pathway. In this study their respective contributions toward formation of dolichols in Coluria geoides hairy root culture were estimated using in vivo labeling with 13 C-labeled glucose as a general precursor. NMR and mass spectrometry showed that both the MVA and MEP pathways were the sources of isopentenyl diphosphate incorporated into polyisoprenoid chains. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 58 publications
4
52
0
Order By: Relevance
“…On the other hand, quantitative analysis of the intensity of 13 C NMR signals is essential for more detailed studies on the biosynthesis of polyisoprenoid alcohols in plants. Recently presented spatial model of the biosynthesis of dolichol in plant cell [22] requires further verification, which is possible by application of the method described in this report. In conclusion, we have shown that the application of 3D TOCSY-HSQC and 3D COSY-HMBC experiments resulted in the full spectral assignment of proton and carbon signals of natural abundance prenol-10.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, quantitative analysis of the intensity of 13 C NMR signals is essential for more detailed studies on the biosynthesis of polyisoprenoid alcohols in plants. Recently presented spatial model of the biosynthesis of dolichol in plant cell [22] requires further verification, which is possible by application of the method described in this report. In conclusion, we have shown that the application of 3D TOCSY-HSQC and 3D COSY-HMBC experiments resulted in the full spectral assignment of proton and carbon signals of natural abundance prenol-10.…”
Section: Resultsmentioning
confidence: 97%
“…[17] More accurate assignments have yielded many applications including analysis of compounds with a very large number of isoprene units [18 -21] and accurate tracing of biological pathways in dolichols. [22] Worth noting are 3D models of dolichol-19 and dolichyl-19 phosphate, which were based on 2D 1 H-NMR nuclear Overhauser enhancement spectroscopy (NOESY) results and refined by energy minimization with respect to all atoms using the assisted modelling with energy refinements (AMBER) force field, [23] even though the nuclear Overhauser effect (NOE) constraints used in structural calculations were from broad CH 3 and CH 2 signals.…”
Section: Introductionmentioning
confidence: 99%
“…The MVA pathway is present in the majority of organisms, including yeasts [14], animals [15] and some gram-positive bacteria [16], whereas most gram-negative bacteria (e.g., Escherichia coli and Bacillus subtilis) [17] and green algae use only the MEP pathway [18]. In plants both pathways, the MVA and MEP are used to synthesize dolichols [19]. dominating [20 -22], while upon exponential growth only the former family is detectable.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…dehydrodolichols) [2]. Dolichols have been detected in mammalian and yeast cells and recently in plant roots [4,5]. An interesting feature of the polyisoprenoid alcohols of a given organism is their occurrence as a mixture commonly named 'family'.…”
Section: Introductionmentioning
confidence: 99%
“…While almost all the enzymatic steps of polyisoprenoid and phytosterol biosynthetic pathways have already been well described [3,5,19,20,21,22], the general mechanisms coordinating the isoprenoid metabolism with the cellular metabolic network are still a subject of extensive studies. One of the well recognized signaling molecules is glucose and hexokinase-dependent and hexokinase-independent signaling pathways are known to participate in sugar sensing [23].…”
Section: Introductionmentioning
confidence: 99%